Relationship of anatomical lengths of forearm plus hand to the length of femur in healthy subjects - Mohd Salahuddin Ansari; Tarun G; Shobha SA; Rashmi M (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
The commonest procedure for adult diaphyseal femoral fractures is intramedullary nailing. A thorough preoperative examination of facture pattern and its morphology are necessary. Previous studies are non-homogenous and with conflicting results. So the study was planned to find out, any relation between femur and forearm plus little finger length and its association with height/ arm span and upper segment/lower segment ratios in an individual, with its statistical validity. The study was carried on 75 male and 75 female students of more than 18 years of age, studying at AIIMS Rishikesh after taking their informed consent and ethical approval. The forearm plus hand length and the length of femur were measured as per protocol, by simple measuring tape. The mean forearm plus hand length and the length of femur were 42.85 (SD, ±1.87) and 45.88 (SD, ±2.95) cm, respectively with the mean difference between these 2 measurements of -3.03 (95% CI, -3.83 to -2.22) cm, in male and 39.56 (SD, ±1.68), 40.96 (SD, ± 2.75) cm and -1.400 (95% CI, -1.917 to -0.883) cm in female volunteers. The Pearson correlation co efficient and p value 0.575, 0.0001 and 0.585, 0.0001 in male and female respectively. There was no significant variation with height, upper segment and lower segment ratios. So we conclude that there is extremely significant correlation between the forearm plus hand length and the length of femur of the individuals. The forearm plus hand length represents the maximum length of the nail to be used in femur. The length of the femur nail can be definitely predicted by the forearm plus hand length in both sexes but it has to be different in both, for the same femoral fracture and there is no significant variation in the femur length with height, upper segment and lower segment variation in the same individual.